Investigation into the Pathophysiology and the Objective Neurophysiological Measurement of Cancer-Related Fatigue in a Pre-Treatment Cancer Cohort - O'HIGGINS, CIARA MARIE (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Cancer-related fatigue (CRF) is one of the most common, debilitating, highly prevalent and unrelenting symptom experienced by patients through all stages of the cancer trajectory and often into survivorship (Berger et al., 2015a; Barsevick et al., 2010). Two factors, central and peripheral, can contribute to fatigue in CRF sufferers. Central fatigue involves difficulty in initiating or sustaining voluntary activities (Davis and Walsh, 2010; Gandevia, 2001), due to challenges with self-motivation, perceived demand and internal biochemical cues, without demonstrable cognitive failure or motor weakness (Davis and Walsh, 2010; Finsterer and Mahjoub, 2014). Peripheral fatigue is caused by failure of either muscle excitation-contraction mechanisms or metabolic changes within the muscle which generally manifest at the affected muscle site and can be described as a progressive loss of power or any exercise induced reduction in the ability to exert muscle force or power. (Davis and Walsh, 2010; Edwards, 1981; Gandevia, 2001; Prinsen et al.). Despite the high prevalence rates, CRF is under-diagnosed and under-treated and perhaps due to its perceived multifactorial nature no universal definition or standard objective measure exists. Current CRF evaluation is based on subjective questionnaires, some of which focus on examining fatigue severity while others address its affective, functional and/or cognitive impact. However, subjective evaluation does not provide insight into the possible underlying aetiologies (cause of CRF) and/or pathophysiology (functional changes as a result of CRF) which remains undetermined and obscured. Therefore, to increase our knowledge and understanding of CRF, a standardised means to objectively assess CRF and its manifestations must be developed. The primary focus of this research was to build on the literature, design and test an objective measurement method employing neurophysiology, electroencephalography (EEG) and electromyography (EMG), which may enhance assessment and help clarify any possible underlying mechanisms of CRF and to address the gaps in the current knowledge about relative contribution of central and peripheral mechanisms, if any. This was to be achieved by examining independent and combined EEG and EMG signal changes for CRF sufferers and healthy controls during a fatigue inducing motor task in a clinical outpatient setting. In addition, the clinical applicability of the objective method in an outpatient clinic was evaluated. The method was assessed in a pre-treatment cancer cohort, which had not been previously examined. In this research, which was carried out over a series of studies, all participants performed a fatigue-inducing task consisting of a sustained isometric contraction at 30% of their maximal force until failure due to fatigue. A hand-held dynamometer was employed in the studies and EEG and EMG were simultaneously recorded during the fatigue-inducing task. The main findings demonstrated that at diagnosis CRF was evident, prior to any fatigue inducing cancer treatment and may suggest a more centrally mediated disorder (i.e. fatigue that originates at the central nervous system (CNS) which decreases the neural drive to the muscle). A metric to objectively evaluate correlates of CRF was developed and its applicability to a routine clinical setting was confirmed. The studies undertaken also provided comparisons between CRF and chronic fatigue syndrome (CFS), sufferers who share overlapping symptoms, onset, and a decreased quality of life. It was hypothesised that these two patient cohorts would show similar results. However, this was not observed, with CFS sufferers recording higher levels of fatigue. A possible explanation for the CFS results was perhaps due to the diagnostic process, whose symptoms must be evident and recorded for six months minimum prior to a diagnosis being confirmed. Another element recognised as relevant to the studies undertaken was that results recorded may be impacted by participants? lack of sustained attention to the task or mind wandering. Cancer patients often describe attentional problems, finding it interferes with their cognitive and motor performance, which in turn may affect their ability to complete the task required within this research. Thus, an important question arose as to whether failure during the task was caused by fatigue or inattention. A retrospective analysis of the EEG data obtained during the fatigue inducing motor task in the CRF showed no difference in what may be considered ?mind wandering? when compared to healthy controls. However, as this was a retrospective study, no direct inference could be made as to whether the individuals did experience mind wandering or if there was comparability between the two groups. Nevertheless, by considering the impact of sustained attention and mind wandering this work highlights another element to be considered in research and what cognitive changes may occur with CRF. In conclusion, an objective method employing EEG and EMG was developed and tested which added to existing measurement knowledge of CRF. This was achieved by examining EEG and EMG signal changes for CRF sufferers and healthy controls during a fatigue inducing motor task in a clinical setting with clinical applicability and participant acceptability recorded. Results of this research demonstrated that CRF and CFS had higher subjective fatigue and both CRF and CFS groups exhibited a reduced ability to perform the motor task and perceived physical exhaustion sooner (Lower MVC and endurance time) than healthy controls. The further development of objective methods of CRF assessment may provide clinicians with objective data which in turn could aid in designing more personalised therapeutic intervention of CRF symptoms and enhance the clinical outcomes of treatment.
APPROVED
Keywords: Fatigue; Cancer-Related Fatigue; Non-Small Cell Lung Cancer; Chronic Fatigue Syndrome